Melting and crystallisation behaviour of soybean oil in blend with palm oil-based diacylglycerol - Ong, C. R. E.; Tang, T. K.; Lee, Y. Y.; Choong, Thomas Shean Yaw; Lai, Oi Ming; Kuan, C. H.; Phuah, Eng Tong (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
In the present work, the physicochemical properties namely fatty acid composition (FAC), iodine value (IV), acylglycerol content and thermal profiles of palm-based diacylglycerol (PDAG) in blend with soybean oil (SBO) at different concentrations (0-100 wt %) were evaluated. The Fourier-transform infrared spectroscopy (FTIR) spectra were determined at mid-infrared region to assign the functional groups. SBO exhibited the same absorption bands as PDAG except at wavelength of 1711, 1450, 1359, 850 and 779 cm-1. This phenomenon indicated that the absorption frequency of the binary mixtures greatly depended on the composition of oil samples. IV of the oil blends was found to decrease from 131.09 ± 0.88 I2/100 g to 51.55 ± 0.60 I2/100 g with increasing PDAG concentrations due to the reduced degree of unsaturation. Generally, binary blends with an increasing PDAG concentration showed a decrease in linoleic acid (C18:2) as well as increase in oleic acid (C18:1) and palmitic acid (C16:0) contents. The DAG content for all the blends increased from 5.15 ± 1.40% to 87.80 ± 0.33% and TAG content decreased from 94.85 ± 1.40% to 12.20 ± 0.33% in tandem with increasing PDAG content. Incorporation of PDAG into SBO significantly affected the crystallisation and melting profiles of SBO.